2020
DOI: 10.1007/s10980-020-01039-z
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood character affects the spatial extent and magnitude of the functional footprint of urban green infrastructure

Abstract: Context Urban densification has been argued to increase the contrast between built up and open green space. This contrast may offer a starting point for assessing the extent and magnitude of the positive influences urban green infrastructure is expected to have on its surroundings. Objectives Drawing on insights from landscape ecology and urban geography, this exploratory study investigates how the combined properties of green and grey urban infrastructures determine the influence of urban green infrastructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Numerous studies use cooling intensity, i.e., the temperature difference between the green space interior and its nearby surroundings, to evaluate the cooling effect of urban green space (Chang et al, 2007;Cao et al, 2010;Kong et al, 2014b). Studies found that urban green space can cool well beyond its own physical boundaries (Upmanis et al, 1998;Cheng et al, 2014;Lin et al, 2015;Andersson et al, 2020). However, few studies quantified how far the cooling effect of urban green space could reach.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies use cooling intensity, i.e., the temperature difference between the green space interior and its nearby surroundings, to evaluate the cooling effect of urban green space (Chang et al, 2007;Cao et al, 2010;Kong et al, 2014b). Studies found that urban green space can cool well beyond its own physical boundaries (Upmanis et al, 1998;Cheng et al, 2014;Lin et al, 2015;Andersson et al, 2020). However, few studies quantified how far the cooling effect of urban green space could reach.…”
Section: Introductionmentioning
confidence: 99%
“…It is consequently such areas that could pose a priority for intervention, and by bringing such potential hot spots to the attention of decision-makers, timely and proactive instead of rather reactive adaptation measures might be taken. In the case of heat stress, for instance, greening measures could be implemented for heat adaptation in evolving hot spots with low green space accessibility and thus lack of cooling potential (Andersson et al, 2020;Haase et al, 2019). Similarly, in the case of flooding, the implementation of both structural as well as non-structural (behavioural) flood protection measures may be facilitated.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Ikin, et al [51] found that overall bird richness and abundance in small urban parks in Canberra, Australia, had consistently negative responses to increasing residential density. On the other hand, on a landscape scale study assessing how receptive different land uses are to the influence of neighbouring green spaces in Leipzig, Andersson, et al [52] found a statistically significant declining impact of green space on bird species richness outside its boundaries and also that built-up density has a significant impact on the functional footprint of urban green infrastructure; however, they suggested that that, depending on the existence of functional connections, a dense city can provide suitable habitat for specific breeding birds.…”
Section: Biodiversitymentioning
confidence: 99%